The role of multispiral computed tomography in detecting and the assessment of the degree of damage of esophago-gastric junction cancer - V. N. Diomidova; A. N. Dmitrieva (Исследования и практика в медицине)
Purpose of the study. To find out the abilities of multispiral computed tomography (MSCT) using intravenous bolus injection in detecting and preoperative esophago-gastric junction cancer staging in order to improve preoperative diagnosis of this pathological condition.Materials and methods. The patients, diagnosed esophago-gastric junction cancer (n1 = 76), esophagus (n2 = 27) and medically fit people’s (n3 = 30) findings of investigating have been analyzed. All patients went through computed tomography on Light Speed VEX Plus and Light Speed RT 16 ("GE", The USA). The findings of MSCT have been compared with anatomical data, which were got after histomorphologic study of post-operation and endoscopic recruitment material.Results. Characteristic MSCT signs of the wall of the esophageal-gastric junction (EGJ) were revealed in healthy individuals, with esophagitis and cancer. The thickness of esophagus paries in normal conditions and in case of esophagitis and EGJ cancer is: 5.4 ± 1.01 mm, 10.36 ± 1.85 mm, 22.53 ± 8.19 mm (p < 0.001). The external diameter of the abdominal part of esophagus in the normal condition is 14.2 ± 1.68 mm, in case of esophagitis is 17.96 ± 3.7 mm, EGJ cancer is 27.9 ± 9.48 mm (p < 0.001). The main statistically significant (p < 0.001) qualitative character of esophago-gastric junction canser were: non-visualization of mucic in afflicted areas (96.8 %), bosselated upper and lower contours of narrowing (75.2 %), dissymmetric parries pachymenia (70.4 %), blunt-edged outer contours (58.4 %), cotyloid suprastenotic esophageal distensibility (45.6 %). The delicacy depended on the degree of damage delicacy and was at the stage Т1 – 66.7 %, Т2 – 76.5 %, Т3 – 77.8 %, Т4а – 86.2 %, Т4b –100.0 %, in general, diagnostic accuracy of the method in EGJ cancer Т-staging was 81.6 %.Conclusion. The results of the work showed that the inclusion of MSCT with intravenous bolus contrast in the algorithm of the study of patients with suspected tumor pathology of the EGJ will improve the diagnosis of cancer of the EGJ.